MARKETING PROCESS STRATEGY AND COMPETITIVE ADVANTAGES OF PHARMACEUTICAL FIRMS IN LAGOS, NIGERIA - Nurudeen Bello Ahmed; Yusuf Ismail; Afolayan Anthony Kehinde (Sampoerna University, 2026)
In an increasingly competitive pharmaceutical market, firms are required to adopt efficient operational processes to sustain competitive advantage and improve organizational performance. This study examined the effect of process strategy dimensions, specifically process standardization and technological integration, on the competitive advantage of pharmaceutical firms in Lagos State, Nigeria. The study adopted a cross-sectional survey research design, with data collected through structured questionnaires administered to employees of selected pharmaceutical firms. A total of 360 valid responses were analyzed using descriptive statistics and multiple regression analysis with the aid of SPSS version 27. The findings revealed that pharmaceutical firms demonstrated a high level of implementation of process strategy practices. Regression results showed that process standardization (β = 0.419, p < 0.001) and technological integration (β = 0.401, p < 0.001) both had positive and statistically significant effects on competitive advantage. The model explained 37.7% of the variation in competitive advantage, indicating that improvements in operational standardization and technology adoption significantly enhance firms’ competitiveness. The study concludes that effective implementation of structured operational procedures and the integration of modern technological systems are critical drivers of competitive advantage in pharmaceutical firms. The study recommends that pharmaceutical companies prioritize workflow standardization, digital process automation, and continuous technological upgrading to improve efficiency, regulatory compliance, and long-term competitiveness in Nigeria’s highly regulated business environment.